Enzymatic Hydrolysis of Copra Meal by Mannanase from Streptomyces sp. BF3.1 for The Production of Mannooligosaccharides - . ARIANDI; . YOPI; ANJA MERYANDINI (HAYATI Journal of Biosciences, 2015)
Copra meal contained high polysaccharide mannan. Mannanase Streptomyces sp. BF3.1 efficiently hydrolyzed copra meal to mannooligosaccharides. This research determined the optimum conditions of enzyme mannanase Streptomyces sp. BF3.1 to hydrolyze copra meal. The results of the hydrolysis products were analyzed concentrations of reducing sugars, total sugars and the degree of polymerization. In order to determine the type of product, mannooligosaccharides  were analyzed by thin layer chromatography and high performance liquid chromatography. The mannanase had an optimum condition at 70 °C and pH 6. Optimum conditions of hydrolysis was 10% copra meal concentration with incubation time of 5 h at 30 °C which able to produce a variety of mannooligosaccharides products. Under such conditions, the yield of reducing sugar was 3.83 mg/mL with polymerization degree of 4. Analysis of mannooligosaccharides by thin layer chromatography and high performance liquid chromatography revealed mannobiose, mannotriose, mannotetrose, mannopentose, and mannoheksose.